Effect of constant strain rate, composed of varying amplitude and frequency, of early loading on peri-implant bone (re)modelling - E. De Smet (Blackwell Synergy)
Aim: Examine the effect of varying components of strain rate – amplitude versus frequency – while maintaining a constant strain rate of early controlled mechanical loading on implant stability, peri-implant bone mass and bone-to-implant contact. Material and Methods: Three groups of guinea-pigs received TiO2-blasted implants in both tibiae. One week after installation test implants were loaded 5 days/week during 4 weeks. The contra-lateral implants were the unloaded controls. Strain rate was kept constant (1600 me/s), while amplitude and frequency were varied per group. Implant stability was followed by resonance frequency analysis. Animals were sacrificed, and ground sections were prepared to rate bone-to-implant contact and bone mass. Results: All implants (n578) integrated uneventfully. A significant positive effect (p50.03) of early loading on bone mass was observed in the distal medullar cavity. A significant difference in bone mass between test and control implants was evidenced between the groups (p50.03 and 0.04). A significant increase in implant stability and bone-to-implant contact could not be shown. Conclusions: Early controlled stimulation of peri-implant bone is related to amplitude/frequency and not to strain rate as such, considering a constant stimulation time. An increase of bone mass around early-loaded implants was shown. This cortical bone model is most sensitive to low-frequency/high-amplitude stimulation.